How Big Are the Benefits of Economic Diversification? : Evidence from Earthquakes - Ramcharan, Rodney (IMF Working Papers; Working Paper ;, 2005)
Economic activity is risky. Returns across economic sectors can be highly variable, potentially causing costly adjustments to consumption. However, when returns are imperfectly correlated across sectors and insurance is unavailable, diversification can reduce the economic impact of shocks. Therefore, despite the well-known efficiency benefits from specialization, the risks of too little diversification have long been acknowledged. But how big are the benefits of diversification? This paper exploits the exogeneity and randomness of earthquakes to address this question. There is robust evidence that more specialized economies experience larger declines in consumption when earthquakes occur, and consistent with the insurance channel, the cost of specialization is smaller in more financially developed economies.